Hypochloremia is associated with increased risk of all-cause mortality in patients in the coronary care unit: A cohort study. Issue 4 (April 2020) - Li, Zongying; Xing, Cheng; Li, Tingting; Du, Linxiang; Wang, Na
Objective: Serum chloride disorders have been gaining increased attention. We aimed to assess the impact of serum chloride on all-cause mortality in critically ill patients in coronary care units (CCUs). Methods: We extracted clinical data from the Multiparameter Intelligent Monitoring in Intensive Care III database. We used data for the first CCU admission of each patient; baseline data were extracted within 24 hours after CCU admission. Statistical methods included the Lowess smoothing technique, Cox proportional hazards model, and subgroup analyses. Results: A total 5616 patients who met the inclusion criteria were included. We observed a U-shaped relationship between admission chloride levels and 30-day all-cause mortality. In multivariate analysis adjusted for age, ethnicity, and sex, both hyper- and hypochloremia were significant predictors of risk of 30-day, 90-day, and 365-day all-cause mortality. After adjusting additional clinical characteristics, hypochloremia remained a significant predictor of risk of 30-day all-cause mortality (hazard ratio, 1.47; 95% confidence interval, 1.19–1.83). For 90-day and 365-day all-cause mortality, similar significant robust associations were found. Conclusions: We observed a U-shaped relationship between admission chloride levels and 30-day all-cause mortality among patients in the CCU. Hypochloremia was associated with increased risk of all-cause mortality in these patients.